Nonprofit financial management : a practical guide - Coe, Charles K. (Hoboken, N.J. : Wiley, 2011)
'A timely, practical, and concise handbook of best practices for nonprofit financial management In 2010 an estimated 325,000 charities, membership groups, and trade associations with small nonprofits disproportionately represented?stand to lose their tax exemptions for failure to comply with financial management requirements. Nonprofit Financial Management: A Practical Guide is a timely, functional, and concise handbook of best practices for nonprofit organizations of every size. Addresses federal reporting requirements and discusses methods to decrease expenses, ensure accounting control, increase revenues through professional cash management, and understand budget statements Explains how to read financial statements and analyze a nonprofit's financial condition by using the most recent IRS 990 reporting form Covers the full range of financial-management topics, including accounting, internal controls, auditing, evaluating financial condition, budgeting, cash management and banking, purchasing and contracting, borrowing and risk management Written in an easy-to-read style, with more than 100 exhibits, this book is essential for every nonprofit financial manager.'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Nonprofit organizations -- Finance